A Stride Towards Developing an CBIR System Based on Image Annotations and Extensive Multimodal Feature Set - P. Rachana; S. Ranjitha; H. N. Suresh (International Journal of Computer Sciences and Engineering, 2014)
Content based Image/Video Retrieval system is a querying system that uses content as a key for the retrieval process. It is a difficult task to design an automatic retrieval system because real world images usually contain very complex objects and color information. In this paper, we discuss some of the key contributions in the current decade related to image retrieval and automated image annotation. We also discuss some of the key challenges involved in the adaptation of existing image retrieval techniques to build useful systems that can handle real-world data. so nowadays the content based image retrieval are becoming a source of exact and fast retrieval. In this paper the techniques of content based image retrieval are discussed, analyzed and compared. It also introduced the feature like visual descriptor and ontology methods. The suggestion for feature methodology`s to overcome the difficulties and improve the result performance. In this paper we provide an overview of approaches to CBIR. Major approaches to improving retrieval effectiveness via relevance feedback in text retrieval systems are discussed.